2011
DOI: 10.1128/jcm.00687-11
|View full text |Cite
|
Sign up to set email alerts
|

The N -Acylneuraminate Cytidyltransferase Gene, neuA , Is Heterogenous in Legionella pneumophila Strains but Can Be Used as a Marker for Epidemiological Typing in the Consensus Sequence-Based Typing Scheme

Abstract: Sequence-based typing (SBT) is the internationally recognized standard method for genotyping Legionella pneumophila. To date all strains of serogroup 1 (SG1) and some of SGs 2 to 14 yield a seven-allele profile and can be assigned a sequence type (ST). However, for some strains belonging to SGs 2 to 14, the targeted region of the neuA gene could not be amplified using the published standard primers. We determined the DNA sequence of a neuA gene homolog located in the lipopolysaccharide synthesis locus of strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 21 publications
0
23
0
Order By: Relevance
“…In this study, we identified for the first time two sporadic STs, ST1400 and ST1405, that had the neuAh allele previously only found in non-Lp1 strains of L. pneumophila (26). The ESGLI SBT database showed that ST1400 closely relates to ST12, ST150, ST159, ST221, and 1433, all of which are Lp1 STs that differ from ST1400 at only a single allele, the neuA or neuAh.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we identified for the first time two sporadic STs, ST1400 and ST1405, that had the neuAh allele previously only found in non-Lp1 strains of L. pneumophila (26). The ESGLI SBT database showed that ST1400 closely relates to ST12, ST150, ST159, ST221, and 1433, all of which are Lp1 STs that differ from ST1400 at only a single allele, the neuA or neuAh.…”
Section: Discussionmentioning
confidence: 99%
“…Two of these STs, ST1400 and ST1405, carried the N-acylneuraminate cytidyltransferase homolog (neuAh) typically found in non-Lp1 strains of L. pneumophila and not amplified with the standard neuA primers (26). Both ST1400 and ST1405 contained the same neuAh allele, 207, and this appears to be the first instance of the neuAh allele (in contrast to a typical neuA allele) in Lp1 isolates.…”
Section: Outbreaks With Matching Clinical and Environmental Isolatesmentioning
confidence: 99%
“…For the strains that failed to get neuA amplification, primers targeting neuAh were used as suggested by ESGLI (Farhat et al, 2011). The PCR products were sent to BGI Beijing Inc. for purification and sequencing.…”
Section: Sequence-based Typingmentioning
confidence: 99%
“…These include monoclonal antibody (MAb) subgrouping as a rapid screening method, and various genotyping methods, such as restriction fragment length polymorphism (RFLP) analysis, amplified fragment length polymorphism (AFLP), and pulsed-field gel electrophoresis (PFGE). In contrast to band-based typing methods that are difficult to standardize, the sequence-based typing (SBT) system has the potential to achieve excellent typeability, interlaboratory reproducibility and epidemiologic concordance [3,5,6,7].…”
Section: Introductionmentioning
confidence: 99%